Too Much to Handle? Take Advantage of Working across Multiple Virtual Team Projects - Xiao, Lu (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Fast-forming, fast-dissolving virtual teams have become an important part of the modern organizational life. Managing multiple group projects in the groupware environment is therefore increasingly becoming significant. Prior studies have focused on the negative effects caused by multitasking such as interruption handling and work resumption. In this paper, we discuss the potential positive effects of working across multiple virtual team projects aiming at provoking research directions about management of multiple virtual team projects through collaborative technologies. Les équipes virtuelles éphémères sont une part importante de la vie moderne en entreprise et la gestion de projets de groupe au moyen de collecticiels devient de plus en plus significative. Les études antérieures ont étudié l’effet négatif du fonctionnement multitâche, notamment l’interruption et la reprise des travaux. Dans cette communication, on discute des effets positifs potentiels de travailler au sein de différentes équipes virtuelles dans le but de dégager un axe de recherche sur la gestion de projets de groupe au moyen de technologies collaboratives.